eHealth Literacy and the Use of NHS 111 Online Urgent Care Service in England: Cross-Sectional Survey - Joanne Turnbull; Jane Prichard; Jennifer MacLellan; Catherine Pope (JMIR Publications, 2024)
BackgroundMany health care systems have used digital technologies to support care delivery, a trend amplified by the COVID-19 pandemic. "Digital first" may exacerbate health inequalities due to variations in eHealth literacy. The relationship between eHealth literacy and web-based urgent care service use is unknown. ObjectiveThis study aims to measure the association between eHealth literacy and the use of NHS (National Health Service) 111 online urgent care service. MethodsA cross-sectional sequential convenience sample survey was conducted with 2754 adults (October 2020-July 2021) from primary, urgent, or emergency care; third sector organizations; and the NHS 111 online website. The survey included the eHealth Literacy Questionnaire (eHLQ), questions about use, preferences for using NHS 111 online, and sociodemographic characteristics. ResultsAcross almost all dimensions of the eHLQ, NHS 111 online users had higher mean digital literacy scores than nonusers (P<.001). Four eHLQ dimensions were significant predictors of use, and the most highly significant dimensions were eHLQ1 (using technology to process health information) and eHLQ3 (ability to actively engage with digital services), with odds ratios (ORs) of 1.86 (95% CI 1.46-2.38) and 1.51 (95% CI 1.22-1.88), respectively. Respondents reporting a long-term health condition had lower eHLQ scores. People younger than 25 years (OR 3.24, 95% CI 1.87-5.62) and those with formal qualifications (OR 0.74, 95% CI 0.55-0.99) were more likely to use NHS 111 online. Users and nonusers were likely to use NHS 111 online for a range of symptoms, including chest pain symptoms (n=1743, 70.4%) or for illness in children (n=1117, 79%). The users of NHS 111 online were more likely to have also used other health services, particularly the 111 telephone service (χ12=138.57; P<.001). ConclusionsThese differences in eHealth literacy scores amplify perennial concerns about digital exclusion and access to care for those impacted by intersecting forms of disadvantage, including long-term illness. Although many appear willing to use NHS 111 online for a range of health scenarios, indicating broad acceptability, not all are able or likely to do this. Despite a policy ambition for NHS 111 online to substitute for other services, it appears to be used alongside other urgent care services and thus may not reduce demand.